Being And Worth. - Collier, Andrew (Routledge, 1999)
In Being and Worth Collier argues that beings both in the natural and human worlds have worth in themselves. He builds on recent work in critical realism to provide a reassessment of Spinoza's philosophy of mind and ethics and his conclusions are developed with particular reference to environmental ethics.